Lung function changes from childhood to adolescence: a seven-year follow-up study - Piccioni, Pavilio; Tassinari, Roberta; Carosso, Aurelia; Carena, Carlo; Bugiani, Massimiliano; Bono, Roberto (BMC pulmonary medicine, 2015)
Background As part of an investigation into the respiratory health in children conducted in Torino, northwestern Italy, our aim was to assess development in lung function from childhood to adolescence, and to assess changes or persistence of asthma symptoms on the change of lung function parameters. Furthermore, the observed lung function data were compared with the Global Lung Function Initiative (GLI) reference values. Methods We conducted a longitudinal study, which lasted 7 years, composed by first survey of 4–5 year-old children in 2003 and a follow-up in 2010. Both surveys consisted in collecting information on health by standardized SIDRIA questionnaire and spirometry testing with FVC, FEV 1 , FEV 1 /FVC% and FEF 25–75 measurements. Results 242 subjects successfully completed both surveys. In terms of asthma symptoms (AS = asthma attacks or wheezing in the previous 12 months), 191/242 were asymptomatic, 13 reported AS only in the first survey (early transient), 23 had AS only in the second survey (late onset), and 15 had AS in both surveys (persistent). Comparing the lung function parameters observed with the predicted by GLI only small differences were detected, except for FVC and FEF 25–75 , for which more than 5% of subjects had Z-score values beyond the Z-score normal limits. Furthermore, as well as did not significantly affect developmental changes in FVC and FEV 1, the decrease in FEV 1 /FVC ratio was significantly higher in subjects with AS at the time of follow-up (late onset and persistent phenotypes) while the increase in FEF 25–75 was significantly smaller in subjects with persistent AS (p < 0.05). Conclusions The GLI equations are valid in evaluating lung function during development, at least in terms of lung volume measurements. Findings also suggest that the FEF 25–75 may be a useful tool for clinical and epidemiological studies of childhood asthma.